Review: Perbedaan Penggunaan Pelarut Terhadap Nilai Rendemen yang Dihasilkan dengan Berbagai Metode Ekstraksi dalam Proses Ekstraksi - Nur Latipah Sulistiawanti; Hairunnisa Hairunnisa; Niken Widya Ningrum3; Salma Fitriyanti (An-Najat, 2025)
The extraction process plays a crucial role in isolating bioactive compounds from natural materials. The success of the extraction process is heavily influenced by the type of solvent used and the extraction method applied. This review aims to evaluate the impact of solvents with varying polarities—both polar and non-polar—and compare the efficiency of various extraction techniques, such as Soxhlet extraction, reflux, and Ultrasonic Assisted Extraction (UAE) in obtaining extracts from various medicinal plants. Based on a review of previous studies, polar solvents generally yield higher rendemen compared to non-polar solvents, although non-polar solvents are more effective in selectively extracting non-polar compounds. Therefore, the selection of solvents should be tailored to the type of compound to be extracted to achieve optimal results. The UAE method has been proven to be more efficient than conventional extraction techniques, such as Soxhlet and reflux. The use of ultrasonic waves in UAE enhances solvent penetration into plant cells, resulting in higher yields in a shorter time. Several factors also significantly affect the extraction results, such as the solvent-to-material ratio, extraction time, and temperature. Variations in these three factors can lead to significant differences in both the quantity and quality of the extract obtained. Overall, choosing the right solvent and extraction method is essential for achieving optimal extraction results. By using solvents suited to the properties of the target compounds and selecting the most efficient method, the resulting extracts can be of higher quality and quantity. Therefore, further laboratory research is necessary to apply these findings in developing extraction methods that are not only effective but also environmentally friendly, particularly on an industrial scale. Future research could also focus on developing extraction methods that reduce the use of harmful solvents and enhance the sustainability of the extraction process at an industrial scale.